Case of Fournier’s Gangrene in a Patient with Long-Term Indwelling Catheterization due to Urinary Incontinence after Open Radical Prostatectomy - Kyung Kgi Park; Sung Dae Kim; Young-Joo Kim; Jung-Sik Huh (Urogenital Tract Infection)
Fournier’s gangrene is a life-threatening disease that needs to be treated as soon as possible. An 82-year-old male, who exchanged a urethral catheter once a month for urinary incontinence management after open radical prostatectomy, presented with an acute onset of mental change and general weakness. After ten days’ hospitalization, the disease was diagnosed. The scrotal wall was opened, and the infectious tissue was exposed to the air and kept open with an aseptic dressing. After 45 days, his scrotal wound healed and returned to its typical appearance without scarring and wound disruption. He recovered fully from the infection. This paper reports a case of Fournier’s gangrene in a patient with long-term indwelling catheterization due to urinary incontinence after an open radical prostatectomy with a literature review.